1998
DOI: 10.1159/000023984
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Mechanisms of Human Immune Responses to Bee Venom Phospholipase A<sub>2</sub>

Abstract: The elicitation of an immune response to protein antigens depends on the specific recognition of antigenic determinants (epitopes) by T and B lymphocytes. Bee venom phospholipase A2 (PLA) represents the major antigen/allergen of honey bee venom. It displays three dominant immunogenic peptide and one glycopeptide T cell recognition sites. These epitopes are equally recognized by both allergic and nonallergic individuals. A mixture of the three epitope containing peptides was successfully used in spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
0
34
0
2
Order By: Relevance
“…The transiently downregulated expression of HLA-II during VIT indicates a reduced ability of B cells to present Ag during this time period. It is worth noting that the type of the APC influences the immune response since monocytes enhance, for example, a TH1 response, whereas B cells enhance a TH2 response and IgE production [22, 23]. The fact that B cells are important APCs in situations with low Ag concentrations [24]is also interesting in view of our findings since the cumulative Ag dose is high during the initiation phase of VIT and would support APC other than B cells, and hence TH1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transiently downregulated expression of HLA-II during VIT indicates a reduced ability of B cells to present Ag during this time period. It is worth noting that the type of the APC influences the immune response since monocytes enhance, for example, a TH1 response, whereas B cells enhance a TH2 response and IgE production [22, 23]. The fact that B cells are important APCs in situations with low Ag concentrations [24]is also interesting in view of our findings since the cumulative Ag dose is high during the initiation phase of VIT and would support APC other than B cells, and hence TH1.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies regarding the mechanisms of IT have described allergen-specific effects [2, 25], there is also evidence of allergen-nonspecific effects [3, 22, 26]. These unspecific effects can be partially explained by a reduced IL-4/IFN-γ ratio as described in IT [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of immunotherapy has been proven in several clinical studies (Hunt et al, 1978;Reisman, 1992). In patients undergoing venom immunotherapy (VIT) a shift from a Th2 to a Th1 profile and an increase of the specific IgG4/IgE ratio (Blaser et al, 1998;McHugh et al, 1995;Schuerwegh et al, 2001;Tari et al, 1994) has been observed.…”
Section: Th1 -Th2 Regulation and Allergymentioning
confidence: 99%
“…Bee venom (BV) phospholipase A 2 (PLA) represents the major antigen and allergen of BV [4]. The response to PLA provides a specifically suitable model for studying the cellular and molecular mechanisms of specific immune response regulation in humans [1, 2, 3, 4, 5, 6], reviewed in 7, 8]). In both BV-SIT and peptide immunotherapy (PIT), successfully treated patients showed specific T cell unresponsiveness to the entire PLA allergen as well as to the three T cell epitope-containing peptides [1, 2, 3].…”
Section: A Distinct T Cell Response Profile During Specific Immunothementioning
confidence: 99%